Comprensión lectora según género en estudiantes de 6° grado de primaria de una institución educativa del Callao - Tasayco García, María Elsa (2012)
The investigation was intend to describe and compare different level of reading comprehension according to gender in sixth- grade students in educational institution of Callao. The study group were consisted of 120 students 64 girls and 56 boys, was applied as an instrument for measuring the reading comprehension Test (ACL-6). Authors: G. Catalá, M. Catalá, E. Molina, R. Monclús (2001) adapted by Mr. Ortega and Ps. Ramirez (2009). In the result obtained to showed that skills literal comprehension, reorganization of inferencial don’t difference in gender function. The skills of critical understanding differences in gender function. The skills of the level of reading comprehension in the general test don’t difference in gender function.